(3QSGdI aj Yed GdNWGFjfs - (3ZQS GdOjf GdMdHjs
(3ChdgG (B:s
(3GdMeO ddg YOO fYeGA LdJ Yf GdGMUGA HGdYO CeG HYO agPg QSGdI hLjRI aiYed GdNWGFjf GdHGH GdChd hajg aUhd GdChd ai UhQI GdYed s
(3BNQgG (B:s
(3bOeJG GdeMGHGI Yf GdTGaYi hCHi MfjaI QVi Gddg JYGdi YfgeG hGdYed jYde eeeG JbOe hdjcf gPG BNQ CQOfG GjQGOg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Yde GdaQGFVs